Promoting Interdisciplinary Practice: An Interview With Steven R. Forness - Teagarden, James M.; Kaff, Marilyn S.; Zabel, Robert H. (My University, 2014)
As part of an ongoing oral history project, a conversation was held with Dr. Stephen Forness on the past, present, and possible future of the field of providing services to children with emotional-behavioral disorders. Dr. Forness stresses the increasing importance of providing an interdisciplinary approach to meeting these needs.
Keywords: Special education; Emotional-behavioral disorders; Dr. Stephen Forness